Evaluation of selected herbs extract as repellent against rubber termites (Coptotermes curvignathus) / Ahmad Zaimi Mohd Zawawi and Shazatul Izzati Sha'aree - Mohd Zawawi, Ahmad Zaimi; Sha'aree, Shazatul Izzati (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Termites encompass a various range of destruction of crops and capable of decomposing woods. The widely being used of hazardous chemical pesticides has develop many health problems to the users. Hence, the aim of this study was to substitute the use of hazardous chemical pesticides to herbs based pesticides as repellent agent against rubber termites (Coptotermes curvignathus), which is safer and easier to use. The selected herbs species for this study are lemongrass (Cymbopogon citratus), garlic (Allium sativum) and wild mint (Mentha arvensis). As for C.curvignathus, they were obtained from Forest Research Institute Malaysia (FRIM), Kepong, Selangor, Malaysia. Khaya wood (Khaya senegalensis) (3cm x 2cm x 2cm) is the woods sample that being used. All woods samples were treated with all the selected herbs extract. The repellent testing was conducted for 21 days. The result obtained showed that the three herbs were effective to be used as repellent when compared to percentage weight loss of control, which is 23.58%. The percentages of weight loss of treated groups using aqueous extraction of herbs were 0.61% (lemongrass), 1.56% (mint), and 1.72% (garlic), whereas for methanol extraction of herbs were 0.52% (lemongrass), 1.13% (mint) and 1.55% (garlic). From Analysis of Variance (ANOVA), there is significant different in mean among group with F=275.49, pvalue=0.000<0.05.